Evaluation of antibacterial agents to improve growth rate and efficiency of weaned pigs - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs medicated 5 weeks with TNA-290 and ASP-250 had statistically greater (P<.05) average daily gains and those medicated with ASP-250 had significantly (P<.05) lower feed conversion rations than non-medicated pigs. Feed efficiency, feed consumption, or average daily gain among pigs medicated with Furox, ASP-250, or TNA-290 did not differ significantly.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; Antibacterial agent; Growth rate; Efficiency